2019
DOI: 10.1002/jbm.a.36791
|View full text |Cite
|
Sign up to set email alerts
|

Concentration‐dependent cellular behavior and osteogenic differentiation effect induced in bone marrow mesenchymal stem cells treated with magnetic graphene oxide

Abstract: The scaffold-free cell sheet plays an important role in stem-cell-based regeneration.Graphene oxide (GO) endows nanoparticles (NPs) with special characteristics and therefore has attracted increasing attention in recent years. However, the existence of toxicity in GO and its derivatives limits their ability to promote osteogenic differentiation. Magnetic graphene oxide (MGO), a novel combination of Fe 3 O 4 and GO with diverse unique properties, has not been studied in bone tissue engineering. In this study, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…Magnetic graphene oxide (MGO) decorated by NPs of Fe 3 O 4 was prepared to study cell behavior and the course of osteogenic differentiation, along with the mechanism of the MGO-induced effect, using mesenchymal stem cells derived from rat bone marrow (BMSCs). In conclusion, it was found that MGO, at low concentrations, is biologically compatible and simultaneously notably accelerates osteogenic differentiation in BMSCs [84].…”
Section: Nanotheranostics and Tissue Engineeringmentioning
confidence: 74%
“…Magnetic graphene oxide (MGO) decorated by NPs of Fe 3 O 4 was prepared to study cell behavior and the course of osteogenic differentiation, along with the mechanism of the MGO-induced effect, using mesenchymal stem cells derived from rat bone marrow (BMSCs). In conclusion, it was found that MGO, at low concentrations, is biologically compatible and simultaneously notably accelerates osteogenic differentiation in BMSCs [84].…”
Section: Nanotheranostics and Tissue Engineeringmentioning
confidence: 74%
“…Figure 6a illustrates the cell morphology onto the BS, positive control (0.1% gelatin‐coating), and all scaffolds at different time intervals (24, 48, and 72 h). The attached cells showed ideal cell morphology for the MC3T3‐E1 cell line in which cells were cylindrical with proper cell bodies (He et al., 2020; Khan et al., 2020a). The cells adhered to the bottom of the well have relatively less retained morphologies than the positive control.…”
Section: Resultsmentioning
confidence: 99%
“…57 The concentration of GDs greater than 10 μg/mL might inhibit the proliferation of bone marrow mesenchymal stem cells. 58 Functionalization could decrease toxicity potential of GDs to some extent. 59 In addition, the GDs in sheet structures 60 or compounded with other materials 61 could bring lower toxicity risk because of decreased possibility in penetration into the cell membrane.…”
Section: Introductionmentioning
confidence: 99%